SHADOWS OF SUNDARBANS: UNMASKING CLASS CONFLICT IN BHOMA - Goel, Vrinda; Dwivedi , Akhilesh Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This paper offers a Marxist reading of Badal Sircar’s Bhoma, examining the plight of the marginalised class who harbour for a better future yet face unfulfilled promises from the government. It sheds light on the fact that how the ecological and human habitat of Sundarbans is threatened by the demands of technological advancements and cultivation. It focusses on how Sircar’s Third Theatre challenges and resists capitalist exploitation while advocating for solidarity and collective action among the oppressed. Through this theatre, Sircar aims to move beyond the proscenium theatre to create a more flexible and accessible theatre. According to Marxists, power is monopolised by the dominant class which owns the forces of production. This ruling class uses power to exploit and oppress the proletariat class. In this paper, we intend to reflect upon how theatre becomes a form of resistance against the dominant class and interpret the broader implications of proletariat class to understand the role of marginalised in the contemporary society.